An oral health education programme based on the National Curriculum - A. CHAPMAN, S. J. COPESTAKE & K. DUNCAN (IAPD and Blackwell, 2006)
In recent years, attention has been drawn towards assessing the effectiveness of oral health promotion campaigns. This is in line with demand for evidencebased research and will help to inform policy makers on how to allocate resources.